2021
DOI: 10.1080/19475705.2021.1938703
|View full text |Cite
|
Sign up to set email alerts
|

Droughts over Pakistan: possible cycles, precursors and associated mechanisms

Abstract: In the recent few decades, climate variability had severely affected the socio-economic and environmental conditions worldwide. Frequent shifts in the atmospheric circulation patterns affect large parts of the globe, predominantly the arid and semi-arid regions facing severe to moderate droughts. Therefore, precursors of drought events and their associated mechanisms are important to understand. This study explores the possible cycles and precursor conditions that might be employed for predicting upcoming drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 91 publications
(145 reference statements)
4
33
0
Order By: Relevance
“…The drought degree has increased or decreased in varying degrees from 2010 to 2018, mainly in South Asia and East Asia with wetter dry conditions had become drier and drier, changing to drier conditions, while severe dry conditions in certain areas had changed to wetter conditions. Other relevant studies have also confirmed the accuracy of this result (Ummenhofer et al, 2013;Manolache et al, 2020;Chandrasekara et al, 2021;Hina et al, 2021). In addition, the study of Manolache et al (2020) explored the obstacles of different grassland management measures and the uniqueness to be considered in the selection, which was of great significance to provide different grassland management schemes for grassland ecosystems with different drought degrees.…”
Section: Analysis Of Mann-kendall Test and Sen Trend Degrees In Asian Grassland Ecosystemsupporting
confidence: 62%
See 1 more Smart Citation
“…The drought degree has increased or decreased in varying degrees from 2010 to 2018, mainly in South Asia and East Asia with wetter dry conditions had become drier and drier, changing to drier conditions, while severe dry conditions in certain areas had changed to wetter conditions. Other relevant studies have also confirmed the accuracy of this result (Ummenhofer et al, 2013;Manolache et al, 2020;Chandrasekara et al, 2021;Hina et al, 2021). In addition, the study of Manolache et al (2020) explored the obstacles of different grassland management measures and the uniqueness to be considered in the selection, which was of great significance to provide different grassland management schemes for grassland ecosystems with different drought degrees.…”
Section: Analysis Of Mann-kendall Test and Sen Trend Degrees In Asian Grassland Ecosystemsupporting
confidence: 62%
“…Therefore, the assessment results of trends in drought conditions by the annual data used in this study require further calibration. In addition, several studies showed that drought is caused by a combination of factors such as precipitation, water resources in rivers and lakes, soil moisture content, and soil potential evapotranspiration (Zhang X. Y. et al, 2020;Hina et al, 2021;Su et al, 2021). The TVDI calculated from LST and EVI data in this study could represent the drought of AGE to some extent.…”
Section: Limitationsmentioning
confidence: 99%
“…Overall, the results inferred that most of the stations across Pakistan exhibited a rise in drought severity during Kharif season and annual timescale, especially those located in arid southeastern and northern parts of the region. The increase/decrease in these seasons and overall variability is somehow agreed with the findings of regional studies (Adnan et al ., 2016; Gao et al ., 2017; Ahmed et al ., 2018; Ain et al ., 2020; Hina et al ., 2021). The drought severity and frequency appeared to be shifting from the arid/semiarid regions towards the country's western humid region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to understand possible climate changes implications on crop production, we conducted two separate analyses; the composite and correlational analysis. Reasons for selecting these two analyses is well articulated in [4,77]. Here, the study explored how to combined historical observations of crop production and weather and climate variables to explains crop production.…”
Section: Crop Productions and Its Influencing Factorsmentioning
confidence: 99%